Molecular Characterization of Efflux Pump and Porin Related Genes in Multidrug Resistance Klebsiella pneumoniae Isolates Recovered from Erbil Hospitals (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Multidrug-resistant efflux pumps are one of the most significant methods by which bacteria can evade the effects of numerous antimicrobials. The aim of this study was to determine the prevalence of multidrug-resistant MDR, extremely drug-resistant XDR, and pan-drug-resistant PDR K. pneumoniae phenotypes in clinical isolates, as well as to examine the detection and prevalence of efflux pump genes ompK35, ompK36, tolC, and acrAB in multidrug-resistant K. pneumoniae strains.Materials and Methods: This study was conducted on 60 isolates of K. pneumoniae collected from different clinical samples in Erbil hospitals. The frequency of MDR, XDR, and PDR K. pneumoniae phenotypes was characterized through an antibiotic susceptibility profile, and genes associated with efflux pumps and porins were detected by polymerase chain reaction (PCR) assay.Results: All 60 K. pneumoniae isolates were resistance to one or more classes of antibiotics tested in this study. The maximum resistance was observed with ampicillin (95%), followed by piperacillin acid (83%). Among all isolates the percentage of MDR, XDR, and PDR were (38%), (37%), and (25%) respectively. Furthermore, the distribution of efflux pump genes was acrAB (95%) and tolC (93%), while the prevalence of porin-coding genes ompK35 and ompK36 were (80%) and (82%) respectively.Conclusion: Prevalence of MDR, XDR, and PDR K. pneumoniae strains in Erbil city is worrisome in hospital wards. Furthermore, Genes encoding efflux pump and porins such as acrAB, tolC, ompk35, and ompK36 were highly distributed among all isolates.